Lens-Free Microscopic Imaging for 3D Analysis of Insect Microstructures and Ecological Applications - (Olivia) Ou, Yangxiao (Transactions on Computer Science and Intelligent Systems Research, 2025)
Traditional microscopes provide only 2D intensity information for transparent or unstained samples, limiting access to 3D morphology. Here, we present an in-line lensless digital holographic system using a 532 nm monochromatic light source. The unmodulated direct component serves as the reference wave, and the sample-diffracted component forms the interference, enabling single-frame 3D reconstruction via angular spectrum analysis. The system integrates a board-level CMOS camera with a simplified optical-mechanical structure, alongside automated preprocessing, conjugate suppression, and phase unwrapping. Unified sampling and coherence constraints yield a well-defined effective FOV, allowing quantitative 3D imaging of butterfly antennae and earthworm cross-sections. This low-cost, portable approach bypasses the need for expensive objectives and complex calibration, complementing—but not replacing—high-end instruments. Current limitations include axial calibration and phase noise control; future work will incorporate multi-frame phase shifting, learning-based conjugate suppression, and reflective imaging for strongly scattering samples. This platform provides accessible 3D imaging for entomology, biophotonics, biomimetic materials, and optical device research.
Keywords: Digital Holography; Interferometric Measurement; Three-Dimensional Imaging.